Parallel Synthesis of Cell-Penetrating Peptide Conjugates of PMO Toward Exon Skipping Enhancement in Duchenne Muscular Dystrophy - O'Donovan, Liz (Nucleic Acid Ther, 2015)
We describe two new methods of parallel chemical synthesis of libraries of peptide conjugates of phosphorodiamidate morpholino oligonucleotide (PMO) cargoes on a scale suitable for cell screening prior to in vivo analysis for therapeutic development. The methods represent an extension of the SELection of PEPtide CONjugates (SELPEPCON) approach previously developed for parallel peptide-peptide nucleic acid (PNA) synthesis. However, these new methods allow for the utilization of commercial PMO as cargo with both C- and N-termini unfunctionalized. The synthetic methods involve conjugation in solution phase, followed by rapid purification via biotin-streptavidin immobilization and subsequent reductive release into solution, avoiding the need for painstaking high-performance liquid chromatography purifications. The synthesis methods were applied for screening of PMO conjugates of a 16-member library of variants of a 10-residue ApoE peptide, which was suggested for blood-brain barrier crossing. In this work the conjugate library was tested in an exon skipping assay using skeletal mouse mdx cells, a model of Duchene's muscular dystrophy where higher activity peptide-PMO conjugates were identified compared with the starting peptide-PMO. The results demonstrate the power of the parallel synthesis methods for increasing the speed of optimization of peptide sequences in conjugates of PMO for therapeutic screening.